Interactive 3D visualisation technique used in pulmonary rehabilitation in chronic obstructive pulmonary disease: A randomised controlled study evaluating quality of life, compliance and use of health care - Pernilla Sönnerfors; Anna-Karin Nordlin; Maria Nykvist; Ulrika Thunström; Ulrika Einarsson (Digital Health)
Introduction A pulmonary rehabilitation (PR) programme, including exercise training, education, and behaviour change, is highly recommended in treatment guidelines for chronic obstructive pulmonary disease (COPD). A new PR educational material for PR using an interactive three-dimensional (3D) visualisation technique was developed. There is little known regarding using 3D in this setting. The aim was to evaluate, within a PR programme setting, differences between outcomes of education through interactive 3D compared with education by means of 2D visualisation in patients with COPD regarding health-related quality of life (HRQL), physical capacity, exercise self-efficacy, compliance to exercise training, compliance to medication, and the use of health care and to describe learning styles. Methods Patients were cluster randomised to PR at the University Hospital clinic, including exercise training, for 10 weeks with education by 3D ( n  = 27) or education by traditional 2D technique ( n  = 17). At follow-ups, HRQL, physical capacity, self-efficacy, handgrip strength, compliance to exercise training, compliance to medication and health care utilisation were assessed. Results No significant differences were observed in HRQL in relation to COPD between the groups after 10 weeks. Differences were found in handgrip strength at baseline and at 10 weeks ( p  < 0.01). The 3D group had improved scores in HRQL assessed with the Leicester Cough Questionnaire (LCQ-S) psychological domain ( p  = 0.022). In the 2D group, the LCQ-S social domain ( p  = 0.028), psychological domain ( p  = 0.021) and the St George’s Respiratory Questionnaire total ( p  = 0.050) were increased. The most common learning mode and learning style in both groups was reflective observation and divergent style. Conclusion An interactive education in 3D technique used in a PR programme for patients with COPD yielded no significant differences compared to conventional techniques. Three-dimensional techniques can be used in PR for COPD as an alternative to conventional techniques. ClinicalTrials.gov (identifier:NCT02802618).